2013
DOI: 10.1111/ijn.12205
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, depression, adherence to treatment and illness perception of patients on haemodialysis

Abstract: The purpose of this study was to explore the relationship between quality of life, depression, perception of seriousness of illness and adherence to treatment among Jordanian patients with end stage renal disease on maintenance haemodialysis. The study was carried out using a descriptive, correlation design. A convenience sample of 244 participants was recruited from four major dialysis units in Amman. A self-report questionnaire included demographic data, adherence to treatment and perception of seriousness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
63
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 56 publications
9
63
0
6
Order By: Relevance
“…It shows that the better the patient illness perception, the better the QoL, and the opposite. A previous study had the same results, which showed a significant correlation between illness perception and QoL (Nabolsi, Wardam, & Al-Halabi, 2013;Scharloo et al, 2007;Tiemensma et al, 2016). As examples, identity has moderate and negative correlation with vitality domain (r: -0.431; p: 0.001).…”
Section: Discussionsupporting
confidence: 62%
“…It shows that the better the patient illness perception, the better the QoL, and the opposite. A previous study had the same results, which showed a significant correlation between illness perception and QoL (Nabolsi, Wardam, & Al-Halabi, 2013;Scharloo et al, 2007;Tiemensma et al, 2016). As examples, identity has moderate and negative correlation with vitality domain (r: -0.431; p: 0.001).…”
Section: Discussionsupporting
confidence: 62%
“…As pacientes com doença renal em tratamento hemodialítico relataram que eram constantemente desafiadas por muitos agentes estressores, os quais contribuíam de forma drástica para a redução da qualidade de vida 3,9,16,18 . Logo, dispor de estratégias de enfrentamento é essencial para a se promover a adaptação positiva frente a doença renal e ao tratamento hemodialítico, sendo que, segundo estudos, esses modos de enfrentamento e suporte social estão, geralmente, relacionados ao apoio encontrado nas pessoas e no ambiente 16,18 . Sendo assim, a partir das vivências relatadas pelas pacientes deste estudo, foi possível perceber que tais modos de enfrentamento foram amparados pelo apoio familiar e religioso.…”
Section: Discussionunclassified
“…As limitações da funcionalidade laboral e produtividade profissional destas pacientes pode acabar gerando uma relação de restrição e dependência, ocasionando um desgaste e uma pressão psicológica tanto para a paciente quanto para familiares 20 . Estudos vem afirmando que esse comprometimento laboral, em que a paciente é forçada a um ritual terapêutico repetitivo de longa duração, torna o cotidiano monótono e restrito, dificultando a pessoa a se manter em uma atividade remunerada 3,8,16,18 . Outra alteração cotidiana ocasionada pelo tratamento e pela própria doença renal, evidenciada pelas falas de nossas pacientes, diz respeito à falta de disposição para as atividades diárias e da sensação de cansaço generalizado, que muitas vezes prejudicava as atividades do lar e também as relações familiares, interferindo no convívio com os filhos e com o cônjuge.…”
Section: Discussionunclassified
“…This complex treatment has a high impact on the life of people with CKD. It requires several radical lifestyle changes that afect social and psychological functioning [9] as well as cause pain [7]. Therefore, it is considered a long-term treatment with signiicant side efects on the physical and mental wellbeing [10].…”
Section: Introductionmentioning
confidence: 99%